STRATEGI PEMASARAN SEBAGAI UPAYA MENINGKATKAN PENDAPATAN PELAKU USAHA MIKRO KECIL DAN MENENGAH DI KABUPATEN SUMBAWA - Oktarina, Inez; Usman, U (Samalewa: Jurnal Riset & Kajian Manajemen, 2023)
This study aims to determine the application of marketing strategies as an effort to increase the income of micro, small and medium enterprises (MSMEs) in Sumbawa District. The type of this study is descriptive research with a qualitative approach. The type of data used is qualitative in the form of informants' answers related to the object of research. The qualitative data used in this study were obtained directly from primary sources, namely MSMEs in Sumbawa District using a structured interview technique. The data that has been collected was analyzed using the SWOT analysis technique. The results of this study indicate that MSMEs in Sumbawa Regency have enormous potential to be developed. Through SWOT analysis, information is obtained regarding the strengths, weaknesses, opportunities and threats of MSMEs in Sumbawa District so that appropriate alternative marketing strategies can be formulated that can be carried out as an effort to increase the income of MSME in Sumbawa District. Some of the alternative marketing strategies include the SO strategy which is carried out by exploiting existing strengths and opportunities, the ST strategy which is carried out by utilizing strengths to overcome the threats faced, the WO strategy which is carried out by minimizing weaknesses to be able to take advantage of existing opportunities, and the WT strategy which is done by minimizing weaknesses and threats.